A dialogue between I. Berlin and B. F. Skinner about the concept of freedom - de Paula, William Fernando; Laurenti, Carolina (Perspectivas em Análise do Comportamento, 2020)
Radical behaviorism argues that all human behavior is controlled. For this reason, this philosophy is repeatedly accused of denying human freedom. However, Skinner’s philosophy is not meant to end human freedom and turn humans into machines. In order to clarify the concept of freedom proposed by radical behaviorism in a conciliatory manner with the thesis of behavior control, we sought to establish a dialogue between B. F. Skinner and Isaiah Berlin, who was chosen for systematically discussing the traditional view of individual freedom. Therefore, the purpose of this paper was to outline the relationship between Berlin and Skinner regarding the concept of freedom. Based on the analyzes made, it can be concluded that radical behaviorism does not deny human freedom, as it is often accused of doing. Skinner breaks with the traditional practice of discussing freedom in terms of feelings and subverts his analysis to the contingencies of reinforcement and immediate and future consequences of behavior, which are responsible for circumscribing individuals’ choice. Radical behaviorism goes beyond freedom and has thus been shown to be able to contribute to the widening of individual freedom in its negative and positive sense.